Effectiveness of virtual class for Pre-primary level - Singh, Daman Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
The age of students studying in pre-primary class is 3 to 6 years. Their psychology and comprehension are different from those of adults. The curriculum and lesson plans developed for them differ from those in the adult age group. While teaching them, lessons should be planned by playing games and having fun. Physically present in the classroom and conducting teaching activities will be more effective for the students of this boomer group. To maintain the discipline of the students of this age group in virtual class not so easy. It is difficult to give homework, teaching through different types of learning skills is not difficult, to follow them time is difficult , give necessary instructions is difficult, draw attention to reading and conduct whole-class activities through games and entertainment is also difficult to maintain in a virtual class. This study has clarified that the virtual class for this level of students is not suitable.